Longitudinal Changes in the Brain Following Third Ventriculostomy in a Child With Hydrocephalus: A Case Report. Issue 47 (November 2015) - Li, Yongxin; Zhao, Cailei; Tan, Zhen; Wang, Ya; Zhang, Heye; Wang, Jinyang; Guo, Honghua; Zeng, Baozhen; Huang, Wenhua
Abstract : Abstract: The goal of this study was to detect the long-term effect of shunting on the integrity of white matter in young children with hydrocephalus. The authors reported the case of a 6-month-old boy with hydrocephalus who was evaluated by diffusion tensor imaging (DTI) before and after a shunt operation. When compared with normal children, the structures of the corpus callosum, internal capsule, and corona radiata in the patient showed a decrease in fractional anisotropy and an increase in radial diffusivity values before the shunt operation. Following successful cerebrospinal fluid shunting, long-term follow-up DTI demonstrated a trend toward normalization of the fractional anisotropy and radial diffusivity values. Shunt treatment can prevent further damage to the brain and grossly reconstitute the distorted anatomy. DTI could be a useful tool in detecting longitudinal changes after a shunt operation. Further studies involving larger case numbers are needed to detect the long-term effect of shunting on the brains of children with hydrocephalus.